LA TEMPERATURA DE LA SUPERFICIE DEL MAR PERUANO A PARTIR DE LAS IMÁGENES AVHRR / NOAA (2000 - 2003) - Rojas Acuña, Joel (2006)
The objective of this work is the analysis of the sea surface temperature (SST), estimating of the NOAA / AVHRR data, near the Peruvian coast for their application in the determination of the thermal fronts and in the study of El Niño phenomenon. The study of area is location between the geographies coordinate, (90º W, 0ºS) left upper corner and (70º W, 20º S) right lower corner. The crude image data level 1b LAC and GAC from AVHRR sensor of the NOAA polar orbit satellite’s series has been derived of the NOAA archive active. The Pacha Ricaj software has been designed for read and display the crude image, inverse, geometric corrections execute, cloud filter and SST estimate. The resulting derives are the diary and monthly SST images. In the Peruvian coast, the SST is less in magnitude than off the coast. In this imagines has been observed many cloud over sea and land that have disabled SST estimated. A bias of +1.6% has been calculated and 1.07 ºC of RMSD for this data set.